A novel voltage-mode universal second-order filter using five single ended OTAs and its quadrature sinusoidal oscillator application. (November 2022) - Wang, San-Fu; Chen, Hua-Pin; Ku, Yitsen; Lin, Yi-Chun
This study proposes a single-ended operational trans-conductance amplifier (SEOTA)-based triple inputs and single output high-input impedance voltage-mode (VM) universal second-order filter. The proposed universal VM SEOTA-based second-order filter can be realized for the non-inverting low-pass, non-inverting high-pass, non-inverting band-reject, non-inverting all-pass and inverting band-pass filtering functions by appropriately using different triple-input voltage signals. The high-input impedances of the proposed universal VM SEOTA-based configuration enable the second-order filter to be cascaded without additional buffers. The proposed configuration does not employ external resistors and accordingly is an active SEOTAs and capacitors (SEOTA-C) universal second-order filter. The proposed circuit using two grounded capacitors which is more apposite to further develop into an integrated circuit implementation. The resonance angular frequency and quality factor are orthogonal electronically adjustable. By slightly modifying the proposed universal VM SEOTA-based second-order filter configuration, the VM SEOTA-C quadrature sinusoidal oscillator is achieved. The oscillation frequency and the oscillation condition of the quadrature sinusoidal oscillator can be independently and electronically tuned by adjusting the bias currents of two SEOTAs. PSpice simulation results confirmed theoretic anticipation. The result of the experiment of the commercially available SEOTAs, LT1228s, are also used to verify the characteristics of the proposed universal VM SEOTA-based second-order filter and VM SEOTA-based quadrature sinusoidal oscillator.